Paragorgia arborea Linnaeus 1758 ... - JUAN ARMANDO SÁNCHEZ (Zenodo, 2005)
Paragorgia arborea (Linnaeus, 1758) (Figs. 6–9) Alcyonium arboreum Linnaeus 1758: 803. Paragorgia nodosa Koren & Danielsen 1883 (sensu Bayer 1956: 70). Paragorgia pacifica Verrill 1922: G16. Paragorgia arborea: Broch 1912: 6; Grasshoff 1979: 117 (and references therein). Material examined: NIWA 3308, 33°55.6’S – 167°55.1’E, 1225 m, (Waipori, bottom trawling, Z10987), 23 January 2002, New Zealand; NIWA 3309, (J217), 33°55.6’S – 167°54.4’E, 955 m, (Waipori 1621/011, Z11009) 8 June 2002; NIWA Z10920 (J208)/ Z10956 (J212), (AEX 0101/080), New Zealand EEZ, exact locality unknown (probably near: 42°47’S – 179°32’E, 1077 m), (Kap Farval), 17 October 2001; NIWA 3310, Z9862 (J219), 44° 45.0S –174°50.0–49.0’E, 687–940 m, (Kap Farval 1278/102), 21 October 1999, New Zealand; NIWA 3311, X700 (J221), 35° 50.447’–49.900’S–177° 54.497–54.644’E, “Southern Havre trough” (dredge), 1525–1798 m, 12 February 1996, New Zealand; USNM 98045, 52° 17’– 52° 22’S –160° 40’– 160° 34’E, 659–798 m, (Eltanin R/ V 1414, USAP 16, U. ... : Published as part of JUAN ARMANDO SÁNCHEZ, 2005, Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific, pp. 1-72 in Zootaxa 1014 on pages 15-20, DOI: 10.5281/zenodo.169657 ...